2008
DOI: 10.1002/arch.20266
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localization of storage protein 1 (SP1) in differentiated fat body tissues of red hairy caterpillar,Amsacta albistrigaWalker

Abstract: The accumulation and utilization of storage proteins are prominent events linked to the metamorphosis of holometabolous insects. The female-specific storage protein 1 (SP1) is the major storage protein found in the hemolymph and fat body of female larvae of the groundnut pest, Amsacta albistriga. Here we show SP1 expression and localization in differentiated fat body tissues using biochemical and immunohistochemistry scrutiny. Comparison of A. albistriga SP1 with that of other species with respect to amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 84 publications
1
8
0
Order By: Relevance
“…AalSP1 expression gradually increased from day-1 to day-7 final instar larvae [30]. It has been reported that expression levels of insect storage proteins (including Hex1, Hex2, SP1 and SP2) reach a maximum in the last stage of final instar larvae [31,54]. SeHex and SeSP1 mRNA expression also reached a maximum in the final stage (pre-pupae) of last instar larvae (Figure 3B).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…AalSP1 expression gradually increased from day-1 to day-7 final instar larvae [30]. It has been reported that expression levels of insect storage proteins (including Hex1, Hex2, SP1 and SP2) reach a maximum in the last stage of final instar larvae [31,54]. SeHex and SeSP1 mRNA expression also reached a maximum in the final stage (pre-pupae) of last instar larvae (Figure 3B).…”
Section: Discussionmentioning
confidence: 92%
“…We found that SeHex was expressed not only in fat body and midgut, but also in cuticle and Malpighian tubules (Figure 3A). SP1 in Amsacta albistriga was detected in fat body and pupal ovary [31]. However, the results for SeSP1 reveal that it is expressed in fat body, Malpighian tubules and tracheae (Figure 3A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to numerous up-regulated genes, only two down-regulated genes were detected. SP1 is considered as a storage protein in hemolymph and ovary associated with the development of Lepidoptera insects [34,35]. Another down-regulated gene, chitinase-related protein 1 showed high identity to chitinase.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that insects sequester FAAs into storage proteins in fat bodies and re-release them during metamorphosis to synthesize other proteins (Chandrasekar et al, 2008; Hunt et al, 2003; Wang and Haunerland, 1993; Wheeler et al, 2000), which likely explain this pattern. Tyrosine and tryptophan metabolism increase in Control hosts and are known to play key roles in cuticular sclerotization (Andersen, 2010) and development of the eye (Linzen and Schartau, 1974; Han et al, 2007).…”
Section: Resultsmentioning
confidence: 99%